Design and Implementation of Library Circulation Model of Lagos State University Library (Trinity Journal of Management, IT & Media (TJMITM), 2021)
The beauty of Library operations is not only in the ability to provide needed and useful materials containing information for the community, but also to be able to make them accessible to the clientele as and when needed, which is what circulation is all about. The objectives of the study are, to analyse the existing information system in LASU Library circulation section, design an information model for circulation section of LASU Library, and implementation of the designed library circulation model. The implementation tools used are, HTML (the Hypertext Mark-up Language), CSS (Cascading Style Sheets), Java Script, Jquery, and Mongodb. . The architectural design used is the unified modelling language (UML) which is a general-purpose modelling language in the field of software engineering and provide a standard way to visualize the design of a system. The model will increase the effectiveness and efficiency of the activities carried out at the circulation unit of LASU Library. At the end of the study, recommendations are provided for the smooth run of the designed circulation model.
Keywords: study; library; design; model; query